Malting and Wort Production Potential of the Novel Grain Kernza (Thinopyrum intermedium). (3rd April 2023) - Marcus, Andrew; Fox, Glen
Abstract: As the environmental impacts of beer are of increasing concern to maltsters, brewers, and consumers, perennial cereal crops can offer a more sustainable solution. One new cereal species of interest to the brewing industry is intermediate wheatgrass ( Thinopyrum intermedium subsp. intermedium ), developed by The Land Institute, in Salina, Kansas, U.S.A., under the branded name Kernza®. It has been touted as a more sustainable alternative to barley and wheat in its requirements for less water and nutrient additions and reduced tilling of agricultural fields. To date, no published research has been performed to assess the potential for this grain for the malt and beer industries as a barley replacement. Here, the "M5" variety Kernza grain was micromalted and the finished malt was compared with both the raw grain and to a reference raw and malted barley ( Hordeum vulgare L. var. Copeland). All samples were analyzed for starch gelatinization temperatures via differential scanning calorimetry, amino acid composition, alpha-amylase, diastatic power (DP), total and soluble nitrogen and protein, Kolbach Index (KI), extract, wort free alpha-amino nitrogen (FAN), wort β-glucan, wort color, pH, and clarity. The Kernza malt produced sufficient extract and FAN for typical fermentations with low β-glucan content. However, extract and FAN in the Kernza malts were lower than in the barley reference, and the Kernza worts exhibited higher levels of undesirable soluble protein and haze. Interestingly, the DP for both the raw and malted Kernza were similarly high, indicating that both of the raw grains exhibit high enzymatic activity, which malting did not increase substantially. Results support that Kernza could be an acceptable candidate for malting and subsequent wort production; however, specific techniques may be required to utilize this malt most effectively. Supplemental data for this article is available online at https://doi.org/10.1080/03610470.2022.2026662 .